Hubungan Paritas dengan Kejadian Kekurangan Energi Kronik (KEK) pada Ibu Hamil Di BPM Ny. “A” Desa Gombang Kecamatan Slahung Kabupaten Ponorogo. - Sumini Sumini (Jurnal Delima Harapan, 2018)
There are several factors that occur Chronic Energy Deficiency incident (CED),one of them is parity. Based on preliminary data generated from pregnant women's visitbook in January - December 2016 at BPM Mrs. "A" Gombang Village, Slahung Subdistrict,Ponorogo Regency, 115 pregnant women with K1, 48 pregnant women with anupper arm circumference <23.5 cm, with wires of 28 nullipara, 17 primiparas and 3multiparas. From the incidence of CED cases 50% have abortion and BBLR. This studyaims to determine the relationship parity with chronic energy deficiency incident (CED)in pregnant women in BPM Mrs. "A" Village Gombang Slahung District PonorogoRegency.The type of this research is analytic with retrospective approach using totalsampling technique. The population is all pregnant women who visit Antenatal Care atBPM Mrs. "A" Gombang Village Slahung District Ponorogo Regency from January toDecember in 2016 with the number of 115 pregnant women. The number of samples ofthis study was 115 pregnant women. Method of data analysis using ContingencyCoefficient statistical test with significance determined by value ρ <0,05. The variables ofthis research are parity (independent) and CED (dependent). The measuring tool used inthis study is to use the cohort register of pregnant women.Based on the results of the study, obtained the number of parity in pregnantwomen in BPM Mrs. "A" Gombang Village Slahung District Ponorogo regency almosthalf as many as 45 respondents (39.1%) is primipara. Meanwhile, Chronic EnergyDeficiency incident (CED) in BPM Mrs. "A" Gombang Village Slahung DistrictPonorogo Regency almost half of which is 48 respondents (41.7%) with an upper armcircumference <23.5 cm. So that the value obtained from statistical test ContingencyCoefficient with the significance level of 0.05 is ρ = 0,00 so that ρ <α then H0 is rejectedso that there is relation between parity with Chronic Energy Deficiency incident (CED) inpregnant woman in BPM Mrs. "A" Gombang Village Slahung District Ponorogo Regencyand obtained the value of Contingency Coefficient 0.374 which means the level ofcloseness of the low relationship.In this research, it is expected that the prospective mother and parity make aneffort to pay attention to nutritional condition during pregnancy that is at the time ofAntenatal Care there is measurement of upper arm circle to know whether the mother isrisk of KEK or not, do regulation of food consumption, Hb level examination, Andpregnant upper arm circumference Mother before pregnancy is less than that number,cariudara postponed because do not risk giving birth.